Website-Based Data Processing for Pregnant Women with the "Sejiwa Dengan Jempol" Innovation Program at the Jabon Health Center - Muhammad Fajar Alfian; Ade Eviyanti (Procedia of Engineering and Life Science, 2021)
For pregnant women, patient data is very important for the puskesmas, the patient data as a reference for each pregnancy consultation. such information regarding pregnancy data must be designed in a way that makes it easier to find patient data during pregnancy consultations for specific purposes. sejiwa information system, which is a system that can provide information during pregnancy consultation, nutrition for mothers and children in an agency company. the sejiwa information system is expected to make it easier for the community when pregnancy occurs and does not experience stunting, one of which is by presenting complete patient information and regarding the ongoing sejiwa with jempol innovation program at the jabon health center so that it can be reviewed at any time.